The Effect of Personality Traits on the Expectation Confirmation Model towards Continuance Usage Intention - T., Santhanamery; T., Ramayah (2017)
Recent researchers have focused on investigating the effect of personality traits on the continuance usage intention of consumers. Personality reflects the exceptional features of human beings, the characteristics that defined our essence and reflected in all our thoughts and actions.Eventually, as the usage of internet has shown a tremendous increase world-wide and particularly in Malaysia, it is reasonable to investigate its usage in terms of personality perspectives.Since the level of internet usage is voluntary rather than mandated, so it is more likely to reflect personal motives, needs, values, preferences and other personality attributes. Moreover, past researchers also had predicted that there is a possibility that future technology adoption decision will be more concerned on human nature compared to usefulness factors.As such this research investigated the influence of personality traits (Neuroticism and Agreeableness) towards continuance usage intention.Data was collected using self-administered questionnaires upon those taxpayers who are easily reachable in main cities in Malaysia.Data was analyzed using the Partial Least Squared Method (PLS).Results indicated that agreeableness has a significant relationship towards perceived usefulness and confirmation. Neuroticism has significant relationship towards confirmation but insignificant relationship towards perceived usefulness.